2011
DOI: 10.1002/pmic.201000443
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of urinary exosomes from patients of early IgA nephropathy and thin basement membrane nephropathy

Abstract: To identify biomarker candidates associated with early IgA nephropathy (IgAN) and thin basement membrane nephropathy (TBMN), the most common causes presenting isolated hematuria in childhood, a proteomic approach of urinary exosomes from early IgAN and TBMN patients was introduced. The proteomic results from the patients were compared with a normal group to understand the pathophysiological processes associated with these diseases at the protein level. The urinary exosomes, which reflect pathophysiological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(176 citation statements)
references
References 61 publications
8
166
2
Order By: Relevance
“…These candidates are aminopeptidase N, vasorin precursor, a-1-antitrypsin, and ceruloplasmin. 84 Validation studies are needed, especially to define the predictive role of these potential novel markers. It would also be important to determine whether these proteins within exosomes have causal or protective roles in disease.…”
Section: Glomerular Diseasementioning
confidence: 99%
“…These candidates are aminopeptidase N, vasorin precursor, a-1-antitrypsin, and ceruloplasmin. 84 Validation studies are needed, especially to define the predictive role of these potential novel markers. It would also be important to determine whether these proteins within exosomes have causal or protective roles in disease.…”
Section: Glomerular Diseasementioning
confidence: 99%
“…14 Accordingly, several proteomic studies on urinary exosomes have been performed to identify biomarkers predictive of urinary track diseases, both in experimental and clinical settings. 7,13,[15][16][17][18] For an exhaustive review see Moon et al 19 However no proteomic study of urinary exosomes has been yet accomplished in RCC. Therefore, we performed MS profiling and antibody-based validation and quantification of differential proteins in urinary exosomes from a RCC patient cohort in order to search for a potential tumor marker.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, urinary proteomic profile analysis of IgAN patients suggested that the excreted polypeptides include disease-specific patterns (27)(28)(29). However, these different proteomic strategies, complementary to each other, were restricted to the limited mass range of ion signal m/z,10,000 (27,28) and the tryptic peptides (29).…”
Section: Discussionmentioning
confidence: 99%